CARMA-NRO Orion survey: unbiased survey of dense cores and core mass functions in Orion A - Takemura, Hideaki; Nakamura, Fumitaka; Arce, Héctor G.; Schneider, Nicola; Ossenkopf-Okada, Volker; Kong, Shuo; Ishii, Shun; Dobashi, Kazuhito; Shimoikura, Tomomi; Sanhueza, Patricio; Tsukagoshi, Takashi; Padoan, Paolo; et al. (The astrophysical journal. Supplement series, 2023)
The mass distribution of dense cores is a potential key to understanding the process of star formation. Applying dendrogram analysis to the CARMA-NRO Orion C18O (J = 1-0) data, we identify 2342 dense cores, about 22% of which have virial ratios smaller than 2 and can be classified as gravitationally bound cores. The derived core mass function (CMF) for bound starless cores that are not associate with protostars has a slope similar to Salpeter’s initial mass function (IMF) for the mass range above 1 M ⊙, with a peak at ∼0.1 M ⊙. We divide the cloud into four parts based on decl., OMC-1/2/3, OMC-4/5, L1641N/V380 Ori, and L1641C, and derive the CMFs in these regions. We find that starless cores with masses greater than 10 M ⊙ exist only in OMC-1/2/3, whereas the CMFs in OMC-4/5, L1641N, and L1641C are truncated at around 5-10 M ⊙. From the number ratio of bound starless cores and Class II objects in each subregion, the lifetime of bound starless cores is estimated to be 5-30 freefall times, consistent with previous studies for other regions. In addition, we discuss core growth by mass accretion from the surrounding cloud material to explain the coincidence of peak masses between IMFs and CMFs. The mass accretion rate required for doubling the core mass within a core lifetime is larger than that of Bondi-Hoyle accretion by a factor of order 2. This implies that more dynamical accretion processes are required to grow cores.